ANTIOXIDANT ACTIVITY OF TAUCO ETHANOL EXTRACT AND ITS FRACTIONS - Mustarichie, Resmi; Megantara, Sandra; Indriyati, Wiwiek; Zuchrotun, Ade (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To investigate antioxidant activity and phytochemical screening of ethanol extract, fractions of water, ethyl acetate and n-hexane from tauco. Methods: Two types of tauco was extracted using soxhletation methods, followed by fractionation using liquid-liquid extraction methods and phytochemical screening. Antioxidant activity test was carried out using DPPH with Ascorbic acid (vitamin C) as a reference. Modified method of Farnsworth was applied for phytochemical screening. Results: It was found that extracts of ethanol and ethyl acetate fraction containing flavonoids, monoterpenoid, and sesquiterpenoids whereas the water fraction and a fraction of n-hexane only contain monoterpenes and sesquiterpenoids. The IC50 value for the ethanol extract, water, ethyl acetate, and n-hexane fractions of two taucos in a row were 1192.71 ppm, 1746.01 ppm, 722.38 ppm, 1845.45 ppm and 1190,15 ppm, 1740.30, 710.46, for tauco A and B respectively. Conclusion: It was unexpected that tauco ethanol extract and fractions showed much weaker antioxidant activity than vitamin C, which had the IC50 value of 4.41 ppm. Â